Distributed fault estimation of multi-agent systems using a proportional-integral observer: A leader-following application - Farrera, Béltran; López-Estrada, Francisco-Ronay; Chadli, Mohammed; Valencia-Palomo, Guillermo; Gómez-Penate, Samuel (Zielona Góra: Uniwersytet Zielonogórski)
This paper proposes a methodology for observer-based fault estimation of leader-following linear multi-agent systems subject to actuator faults. First, a proportional-integral distributed fault estimation observer is developed to estimate both actuator faults and states of each follower agent by considering directed and undirected graph topologies. Second, based on the proposed quadratic Lyapunov equation, sufficient conditions for the asymptotic convergence of the observer are obtained as a set of linear matrix inequalities. Finally, a numerical example is provided to illustrate the proposed approach.
Keywords: multiagent systems; fault estimation; state and fault observers; linear matrix inequalities